Políticas públicas de assessoria técnica em arquitetura e urbanismo: práticas na direção da autonomia - Mariana Barbosa Miranda Borel (2020)
This dissertation analyzes public policies and practices of technical services in architecture and urbanism — called Technical Assistance for Housing of Social Interest (ATHIS) or Technical Advisory (AT). Identifies the most relevant aspects and the main characteristics of these work proposals that provide technical support to the low-income population. It places the analysis in the Brazilian context between the 1960s and 2020 and aims to discuss possible alternatives to be built within the State in order to achieve practices with autonomy gains for the population. It has two main focuses that intertwine: public policies and working methods of assistance and technical advice. It identifies that the possibilities of autonomy gains are related to a series of combined factors that, especially in public policies, are complexed by the inherently heteronomous character of the state apparatus and by the cyclical fluctuations in political representations. Aware of this, it works in a logic of understanding the loopholes that make policies and practices possible with some space for building autonomy. Based on this, it elaborates an Evaluation Scheme for ATHIS and AT policies and practices that systematizes nine relevant aspects in relation to the structure of policies and working methods. In raising these aspects, it highlights relevant themes that concerns the provision of technical services in architecture and urbanism in the perspective of autonomy gains. When characterizing them, composing a gradation between heteronomy and autonomy, it reveals that the practices are proposed and executed differently in each case, impacting the processes and the results of the technical work. The clarifications and the guideline provided by the Evaluation Scheme constitute an advance for the analysis of the experiences. It can also be used to guide the elaboration of new policies and work proposals or to indicate which aspects need to be improved. At the end, it presents a propositional exercise for the public technical assistance and advisory program in Belo Horizonte, which is based on the aspects and characteristics organized in the Evaluation Scheme and in the other discussions elaborated throughout the work.